2009
DOI: 10.1111/j.1469-8986.2009.00807.x
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive processes facilitated by contextual cueing: Evidence from event‐related brain potentials

Abstract: Finding a target in repeated search displays is faster than finding the same target in novel ones (contextual cueing). It is assumed that the visual context (the arrangement of the distracting objects) is used to guide attention efficiently to the target location. Alternatively, other factors, e.g., facilitation in early visual processing or in response selection, may play a role as well. In a contextual cueing experiment, participant's electrophysiological brain activity was recorded. Participants identified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
84
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(100 citation statements)
references
References 58 publications
15
84
1
Order By: Relevance
“…Although this view is compatible with our data, it has difficulty explaining previous eyetracking and ERP/MEG data in which repeated displays were associated with significantly fewer eye movements before the target was found (Peterson & Kramer, 2001;Tseng & Li, 2004;Zhao et al, 2012). In addition, the N2pc component of the ERP is greater for old than for new displays (Johnson et al, 2007;Schankin & Schubö, 2009). This component is known to index spatial attention rather than postperceptual decision and response (Luck & Hillyard, 1994).…”
Section: Discussionsupporting
confidence: 46%
See 1 more Smart Citation
“…Although this view is compatible with our data, it has difficulty explaining previous eyetracking and ERP/MEG data in which repeated displays were associated with significantly fewer eye movements before the target was found (Peterson & Kramer, 2001;Tseng & Li, 2004;Zhao et al, 2012). In addition, the N2pc component of the ERP is greater for old than for new displays (Johnson et al, 2007;Schankin & Schubö, 2009). This component is known to index spatial attention rather than postperceptual decision and response (Luck & Hillyard, 1994).…”
Section: Discussionsupporting
confidence: 46%
“…Similarly, scalp event-related potential (ERP) studies have reported a significantly greater N2pc component for repeated than for unrepeated displays approximately 200 ms after display onset (Johnson, Woodman, Braun, & Luck, 2007;Schankin & Schubö, 2009). Because N2pc is an index of spatial attention (Luck & Hillyard, 1994), these differences suggest that contextual cueing affects spatial attention relatively early.…”
mentioning
confidence: 99%
“…This finding has been widely accepted as reflecting a case in which implicit learning affects the attentional system: The learned implicit spatial context guides attention toward the target location (Chun & Jiang, 1998, 1999Chun & Nakayama, 2000;van Asselen & Castelo-Branco, 2009). This finding has been supported by eye movement studies (Manginelli & Pollmann, 2009;Peterson & Kramer, 2001;Tseng & Li, 2004;van Asselen, Sampaio, Pina, & CasteloBranco, 2011) and electrophysiological studies (Olson, Chun, & Allison, 2001;Schankin & Schubö, 2009). Furthermore, the contextual-cueing effect is impenetrable to awareness, and knowledge of the repetition of displays in an experiment changes little with regard to the observed effects.…”
supporting
confidence: 63%
“…Furthermore, because the target appears embedded within distractors, it is not possible to test for perceptual modulations unambiguously. Performance improvements could occur because LTM changed the perception of the target within its familiar context, facilitated retrieval of the configuration of distractors, or facilitated decision making or action selection (Kunar et al, 2007;Schankin and Schubö, 2009).…”
Section: Introductionmentioning
confidence: 99%